ASPEK PEMBENTUKAN AKHLAK MENURUT IBNU QAYYIM AL-JAUZIYYAH - Hasanah Hasanah; Tamarli Tamarli; Irma Aryani; Helena Helena (Jurnal Dedikasi Pendidikan, 2020)
Both the bad character or character of a person is an assessment given by the community to the actions carried out by humans. The parameters of good or bad human deeds are measured based on religious norms, or customs norms of the community itself. Islam determines, that to measure the merits of a human deed is based on religious sharia which is sourced from the revelation of Allah SWT, namely al- Qur'an and hadith of the Prophet. Therefore, anyone who longs for salvation and luck in his life, there is no other way for him except by purifying oneself from the ungodliness and ugliness of his deeds. This study aims to determine aspects of the formation of commendable and despicable morals in the view of Imam Ibn Qayyim Al-Jauziyyah. This research method is (library research) using this analysis method (content analysis) whose main source is the work of Imam Ibn Qayyim Al-Jauziyyah, as for other sources of articles, journals, and other books related to the research topic. Then the results of the study found that the moral aspects according to Ibn Qayyim are divided into several things, he divides the virtues of good morals, among others: Al-Shabru (Patience), Al-Iffah (self-respect), Al-Syaja'ah (courage), and Al -'Adl (fair). And dividing low ethics into four parts. First, al-jahl (ignorance), Second, ad-dhalm (despotism), Third, al-syahwah (lust), Fourth, al-ghadb (anger). And Ibn Qayyim also pointed out the aspects of laudable and despicable, praiseworthy divided into; Having Knowledge and Faith, a clean heart, prioritizing truth and goodness, and making Allah the only One. The aspect of establishing moral disgrace, that is, many people who do not benefit, immersed in dreams, a lot of eating and sleeping, and depending on other than God, then of all aspects will certainly grow and form a good character (mahmudhah) and will also form morals. despicable (mazmumah) in human beings themselves.